2000
DOI: 10.1002/hep.510310230
|View full text |Cite
|
Sign up to set email alerts
|

T(14;18) translocation in chronic hepatitis C virus infection

Abstract: Pathogenic mechanisms of B-cell lymphoproliferative disorders in chronic hepatitis C virus (HCV) infection are unclear. We studied t(14;18) translocation by polymerase chain reaction in peripheral blood mononuclear cells from 50 patients with HCV-related liver disease (group A), 7 with mixed cryoglobulinemia syndrome (group B), 55 with HCV-negative liver disease (group C), and 30 with HCVnegative chronic rheumatic disorders or chronic infection by nonhepatotropic agents (group D). T(14;18) was significantly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 26 publications
1
92
1
3
Order By: Relevance
“…The first one is related to chronic antigenic stimulation with biological auto-immunity (RF and MC) leading to MZL [29,30], which as a result of secondary genetic events, may subsequently evolve towards transformed DLBCL. In de novo DLBCL we could hypothesise that a pro-tumour favourable environment can lead to B cell transformation [31] or that direct HCV infection of B cell may induce transformation [24].…”
Section: Discussionmentioning
confidence: 99%
“…The first one is related to chronic antigenic stimulation with biological auto-immunity (RF and MC) leading to MZL [29,30], which as a result of secondary genetic events, may subsequently evolve towards transformed DLBCL. In de novo DLBCL we could hypothesise that a pro-tumour favourable environment can lead to B cell transformation [31] or that direct HCV infection of B cell may induce transformation [24].…”
Section: Discussionmentioning
confidence: 99%
“…26 Finally, the t(14; 18) translocation has been shown to be present in a significant percentage of peripheral blood lymphocytes in HCV infected individuals, particularly with MC. 27 This translocation is responsible for BCL-2 activation, which extends B-cell survival by inhibiting apoptosis. 28 The major strengths of this study are the large size, and the fact that the cases and controls are population based.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been suggested that HCV-E2 directly activates polyclonal B cells by binding to CD81 (15). Others have proposed that direct HCV infection of B cells may cause oncogenic transformation, particularly through t(14;18) translocation (16,17).…”
mentioning
confidence: 99%